An Experimental Study on the Distribution and Migration of Lubricating Oil in Rolling Bearings at Low Speeds. Issue 4 (4th July 2022) - Liang, He; Zhang, Yu; Wang, Wenzhong; Zhang, Shengguang
Abstract: Lubrication is very important for good working performance and long life for rolling bearings. The distribution of the lubricating oil layer outside the ball-raceway contact directly determines the formation of the lubricating oil film in the contact area. A bearing model test rig was built with the outer ring replaced by a glass one so as to realize the direct observation and measurement of the oil layer outside the ball-raceway contact area by photography. The migration of lubricating oil on the outer ring, steel ball, and cage under low speed was mainly studied. The influence of working-condition parameters such as time, speed, oil supply, and viscosity of lubricating oil was investigated.